Epidemiological studies on stem rot of chickpea - and B.K. SHARMA, S.K. SHARMA, P.N. SHARMA (Indian Phytopathology, 2002)
Investigation were carried out on epidemiology of stem rot of chickpea [Sclerotinia sclerotiorum (Lib.) de Bary] in relation to weather variables during the Rabi season of 1993 and 1994 at Regional Research Station Dhaulakuan. The two year-study revealed that the appearance of disease coincided with post-blossoming stage of the crop. Both maximum and minimum temperature (22.1-S.4Â°C) high relative humidity (71.84%) and rainfall ranging between 26.4- 38.0 mm played a significant role in the development of the disease. However, the period of maximum incidence coincided with high rainfall and relative humidity along with moderate temperature during both the years. The relationship between weather variables and disease progress was further established by determining correlation-regression analysis indicating 74-84 per cent variation in the disease incidence due to cummulative effect of the various weather variables taken into account during the course of investigations.